2017
DOI: 10.1002/app.44895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the chain‐extender content on the structure and performance of poly(lactic acid)–poly(butylene succinate)–microcrystalline cellulose composites

Abstract: Composites of poly(lactic acid) (PLA) with poly(butylene succinate) (PBS) and microcrystalline cellulose (MCC) as reinforcements of the polymer matrix were prepared by melt blending to improve the brittleness of PLA. As a reactive compatibilizer, a chain extender was used in an attempt to solve the composites’ interfacial problems and to improve their mechanical properties; Fourier transform infrared spectroscopy indicated that the chain extender functionally reacted with PLA, PBS, and MCC mainly through end c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…As a result, consistent filaments were successfully extruded and the processing window for 3D printing was widened such that the blends could be printed at higher temperatures. Based on preliminary evaluation and existing research 16,17,24,25 , as well as taking the biocompatibility into consideration, a low amount of CE (0.25 parts per hundred-phr) was selected for this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, consistent filaments were successfully extruded and the processing window for 3D printing was widened such that the blends could be printed at higher temperatures. Based on preliminary evaluation and existing research 16,17,24,25 , as well as taking the biocompatibility into consideration, a low amount of CE (0.25 parts per hundred-phr) was selected for this study.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, consistent filaments were successfully extruded and the processing window for 3D printing was widened such that the blends could be printed at higher temperatures. Based on preliminary evaluation and existing research 16 , 17 , 24 , 25 , as well as taking the biocompatibility into consideration, a low amount of CE (0.25 parts per hundred—phr) was selected for this study.
Figure 1 The optimization of 3D printing parameter and 3D printed samples: ( A ) the effect of chain extender on the melt-extrusion filament performance (PHBV:PLA (40:60) blend); ( B ) the effect of temperature on the complex viscosity of PHBV:PLA:CE (40:60:0.25) blend; ( C ) the effect of printing speed on the complex viscosity of PHBV:PLA:CE blends; ( D ) the 3D printed PHBV:PLA:CE (40:60:0.25) tensile and flexural bar at optimized temperature and printing speed.
…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon proved the aforementioned reaction of CE and PLA/PPC and had the effect of increasing the chain length and relative molecular weight and even producing long branches to increase the width of the molecular weight distribution. Meanwhile, the increase in storage modulus revealed the improvement in melt strength, and it was beneficial for polymer processing such as blow molding …”
Section: Resultsmentioning
confidence: 99%
“…28 Recently, many authors have shown the interest on using a chain extender, which is multifunctional additives that bind to the ends of different macromolecular fragments (carboxyl and hydroxyl groups in polyesters), thus extending the chain, increasing the average molar mass of the polymer, and also can be used as a reactive compatibilizer in blends. [29][30][31] The chain extender used in blends promotes the formation of copolymers during compounding in the molten state. It acts as the physical compatibilizer by reducing the size of the dispersed phase.…”
mentioning
confidence: 99%